The Influence of Leadership, Education, Mutations on Teacher Career Development - Aprizal Wahyudi Diprata; Ahmad Syukri; Kasful Anwar Us (DINASTI RESEARCH, 2021)
This article discusses and analyzes the influence of education, training and transfers on teacher career development, as additional insight for teachers and prospective teachers so they can understand matters that influence career development. The method of writing this Literature Review article uses library research methods sourced from online media such as Google Scholar, Mendeley and/or other academic online media. The results of this article are: 1) Leadership influences teacher career development; 2) Education influences teacher career development; and 3) Mutations affect teacher career development. In addition to these 3 exogenous variables that affect the endogenous variables in the placement of subordinates, there are many other factors including training, promotion, competence and work environment.